THE ROCK COMPRESSIBILITY CHARACTERISTICS OF SOME INDONESIAN RESERVOIR LIMESTONES - Bambang Widarsono (Testing Center for Oil and Gas LEMIGAS, 2014)
Rock compressibility is an important formation rock properties. It infl uences various processesin reservoir and rock formations that encompass from sources of reservoir driving energy, changes inother reservoir properties, to land subsidence. Various studies have been performed and published, butno comprehensive studies have ever been performed on Indonesian reservoir rocks. This article presentsresults of such studies on Indonesian limestones, reservoir rocks that have contributed much to Indonesia’snational oil and gas production for decades. The study was carried out in order to study the characteristics oflimestone in its relation to rock porosity. A set of 84 limestone samples taken from fi ve productive formationsin Indonesia is used in the study. Some existing and widely known mathematical correlations/models are alsoused to assist the study. Some of the results show that the existing models are not always valid for some ofthe rocks, and therefore a new model is proposed for medium-hard and vuggy limestones. The results alsoshow that limestone characteristics are not related to rock types and place of origin, but instead to rockhardness and degree of vuggy pore presence.